"The First Step Is to Bring It Into Our Hands:" Wild Seed Conservation, the Stewardship of Species Survival, and Gardening the Anthropocene at the Millennium Seed Bank Partnership. (26th November 2019) - Lewis‐Jones, Kay E.
Abstract: Conserving wild plant seeds at the Millennium Seed Bank Partnership (MSBP) provides insurance by facilitating the reintroduction of threatened species. However, seed bank collections also provide an easily accessible resource for research into innovative conservation approaches and the adaptive management of natural resources and landscapes. In this regard, the MSBP corresponds with an emerging body of practice dubbed "New Conservation" that responds to the environmental implications of the Anthropocene and introduces the prospect of "gardening" nature. By examining the attitudes expressed by seed bank staff in the UK and United States. This article illustrates their awareness of the tension between the need to mitigate species extinction and the anthropocentrically governed, or gardened, form that the species' survival might subsequently take. Those within the MSBP were often thoughtfully engaged with the ideological questions their practice raises. However, external expectations of what seed bank collections facilitate, such as those of funders, will also impact how these collections are used. These expectations present selective pressures that risk limiting and thus filtering which species are reintroduced from the bank and the form in which their place in the world is forged.